Scoping review of the existing technical guidelines for designing, implementing, and tracking climate adaptation policies: Gaps, opportunities, and entry points - Odhiambo, Isaack; Njuguna, Lucy; Mundia, Carolyne; Kimanzi, Meshack; Akoko, Tessie; Binge, Brenda; Kung'u, Fredrick; Denje, Telvin; Chilambe, Pedro; Wamukoya, George (2025)
African countries continue to face persistent challenges in translating climate policy commitments into effective adaptation action despite growing engagement with the global climate commitments. This scoping review assesses the extent to which existing international and regional climate policy technical guidelines relevant to the African context, support the design, implementation, and tracking of climate adaptation policies. Using a PRISMA-ScR- approach, the study reviewed the existing climate policy guidelines published between 2015 and 2025 and assessed them across four thematic areas: Policy Design, Implementation, Tracking (Monitoring, Evaluation, and Learning), and Cross-cutting dimensions. Quantitative scoring was complemented by qualitative synthesis and validated through peer-to-peer learning with practitioners from 11 African countries. The results from the assessment presents a strong conceptual articulation in Policy Design and Cross-cutting principles, particularly in objective clarity and alignment with global frameworks. However, significant gaps persist in implementation readiness (financing, institutional coordination, technology transfer) and tracking systems (baseline setting, attribution, data integration), underscoring the need for operational, context-specific guidelines to bridge policy ambition and effective climate adaptation outcomes in Africa.